Real-time middleware for cyber-physical event processing - Chao Wang; Gill, Christopher; Chenyang Lu (2017 IEEE/ACM 25th International Symposium on Quality of Service (IWQoS), 2017)
Cyber-physical applications are subject to temporal validity constraints, which must be enforced in addition to traditional QoS requirements such as bounded latency. For many such systems (e.g., automotive and edge computing in the Industrial Internet of Things) it is desirable to enforce such constraints within a common middleware service (e.g., during event processing). In this paper, we introduce CPEP, a new real-time middleware for cyber-physical event processing, with (1) extensible support for complex data processing operations, (2) execution prioritization and sharing, (3) enforcement of absolute time consistency with load shedding, and (4) efficient memory management and concurrent data processing. We present the design, implementation, and empirical evaluation of CPEP and show that it can (1) support complex operations needed by many applications, (2) schedule data processing according to consumers' QoS requirements, (3) enforce temporal validity, and (4) reduce processing delay and improve throughput of temporally valid events.